Traction alopecia revealed by white hair casts. - Lopes de Magalhães, T.; Poço Miranda, S.; Bernardo, D.; Azevedo, A. (European Journal of Pediatric Dermatology, 2024)
Traction alopecia (TA) refers to thinning hair caused by prolonged or repeated strain on hair follicles. Hairstyles associated with a higher risk of TA are common in early childhood, particularly among women. The case was presented of an otherwise healthy 7-year-old girl treated for a long time for pediculosis and seborrheic dermatitis, in which the dermoscopic demonstration of white hair casts led to the diagnosis of traction alopecia. Recognizing TA in its early and reversible phase in the pediatric population is essential, since timely interventions and counseling can prevent permanent cicatricial alopecia.